2020
DOI: 10.21608/edj.2020.77550
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone modulates the inflammatory and apoptotic pathways incorporated in fluorouracil-induced oral mucositis in rats

Abstract: Introduction:Oral mucositis (OM) is a well-known complication of radiotherapy (RT) and chemotherapy (CT) in cancer patients. Although, 5-flourouracil (5-FU) is one of the standard cytotoxic therapies, it is one of the most common causes of OM, which results in delay, dose reduction or treatment discontinuation, thus this intensifies the need for an effective chemoprotective agent. We aimed to investigate the potential chemoprotective effect of growth hormone (GH) on 5-FU-induced OM in rats. Material & Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…Our results confirmed the previous studies, which reported that 5‐FU caused marked loss of body mass and intestinal inflammation. [ 46–48 ] The present work revealed a significant correction of histopathological changes, improvement of body weight decreases, and reduced water intake induced by 5‐FU upon concurrent treatment with thymol in either dose confirming its protective effect. The dose of 120 mg/kg showed greater protection as revealed by histopathological examination.…”
Section: Discussionsupporting
confidence: 72%
“…Our results confirmed the previous studies, which reported that 5‐FU caused marked loss of body mass and intestinal inflammation. [ 46–48 ] The present work revealed a significant correction of histopathological changes, improvement of body weight decreases, and reduced water intake induced by 5‐FU upon concurrent treatment with thymol in either dose confirming its protective effect. The dose of 120 mg/kg showed greater protection as revealed by histopathological examination.…”
Section: Discussionsupporting
confidence: 72%
“…Upon its administration, patients may suffer from oral mucositis and IM as a drawback, worsening patients' life quality. This could lead to the discontinuation of the chemotherapy [2,21].…”
Section: Discussionmentioning
confidence: 99%
“…With a very high incidence and fatality rate, cancer is one of the most lethal diseases that affect humans (Al Serwi et al 2020 ). However, the majority of currently available medications have serious side effects and are frequently unsuccessful as a result of the emergence of chemo-resistance (Kunnumakkara et al 2019 , Halcrow et al 2021 ).…”
Section: Pharmacotherapeutic Actions Of Basmentioning
confidence: 99%
“…Multiple cases and fatalities from cancer were attributed to hepatocellular carcinoma (HCC) each year (Vogel et al 2022 ). When the effects of BA were examined, it was discovered that in liver cancer cells, they induced apoptosis and inhibited proliferation via the caspase-8-dependent signaling pathway (Liu et al 2002a , Al Serwi et al 2020 ). Additionally, BA increased levels of caspase-3 activity (Fig.…”
Section: Pharmacotherapeutic Actions Of Basmentioning
confidence: 99%